Comparison of the properties of polyimide nanocomposites containing three different nanofillers: Organoclay, functionalized graphene, and organoclay/functionalized graphene complex. (October 2015) - Kwon, Kidae; Chang, Jin-Hae
Polyimide nanocomposites containing three different types of nanofillers were compared in terms of their thermal properties, morphology, and oxygen permeability. Organically modified hectorite clay (STN), functionalized hexadecylamine-graphene sheets, and an STN/hexadecylamine-graphene sheets complex were utilized as nanofillers in the fabrication of polyimide nanocomposite films. Hybrid films were obtained from blended solutions of the precursor polymer and the three types of nanofillers, and the filler content with respect to the polyimide was varied from 0 to 20 wt%. The variations in the properties of the polyimide matrix with respect to the filler content are discussed. Transmission electron microscopy photographs confirmed that most of the STN and hexadecylamine-graphene sheets were dispersed homogeneously throughout the matrix polymer on the nanoscale, although some agglomerate STN/hexadecylamine-graphene sheet complex particles were also formed. The coefficients of thermal expansion and the O2 transmission rates of the hybrid materials were found to improve linearly as the filler content of the polyimide matrix increased.